Olanzapine: Association Between a Typical Antipsychotic Drug and Aortic Calcification - Zhang, Chao; Zheng, Dongdong; Feng, Weijing; Zhang, Huanji; Han, Feng; He, Wanbing; Liu, Aiting; Huang, Hui; Chen, Jie (Frontiers in Cardiovascular Medicine, 2021)
Aims: This study concentrates on the relationship between antipsychotic drugs (APDs) and aortic calcification. Methods: All 56 patients with schizophrenia were divided into 2 groups according to aortic calcification index. APD equivalent dose was calculated via defined daily doses method. Results: In schizophrenia patients with higher aortic calcification index score, APD equivalent dose was lower. And APD equivalent dose was negatively related to aortic calcification index. Although equivalent APD dose in patients without olanzapine treatment was negatively related to aortic calcification index, it seems that equivalent APD dose did not associate with aortic calcification. Conclusion: Aortic calcification is negatively associated with APD dose in schizophrenia patients. Olanzapine seems to be one vital for the relationship between aortic calcification and APD treatment.